Cacao shell-derived solid acid catalyst for esterification of oleic acid with methanol. (August 2019) - Bureros, Glorie Mae A.; Tanjay, April A.; Cuizon, Dan Elmer S.; Go, Alchris W.; Cabatingan, Luis K.; Agapay, Ramelito C.; Ju, Yi-Hsu
Abstract: Cacao shell-derived solid acid catalyst (CS-SAC) was successfully prepared by partial carbonization followed by sulfonation at various temperature (80, 100, 120 °C) and time (4, 6, 8 h) settings. The catalysts were analyzed for their acid densities and tested for their activity in the esterification of oleic acid with methanol at 45 °C for 4 h, with methanol to oleic acid molar ratio of 7:1 and a catalyst loading of 5 %w/w. It was found that increasing the sulfonation temperature at sulfonation times of 4 and 6 h increased the solid's total acid density and sulfonic acid density thereby increasing its specific catalytic activity. Prolonging sulfonation time at any temperature, however, had no significant effect. The highest specific catalytic activity of 14.0 mmol FAME·g −1 CS-SAC·h −1, which corresponds to 79% conversion of oleic acid was observed for SAC sulfonated at 120 °C for 4–6 h. Prolonged esterification up to 24 h resulted in high conversion of ∼94% even at a low temperature of 45 °C. Although the catalyst was later found to decrease in its activity during reuse, its catalytic activity remained stable after the 3rd cycle at a conversion of 48% of the oleic acid. Highlights: Partially carbonized csacao shells as catalyst support in the synthesis for solid sulfonic acid. Sulfonation carbonized cacao shell are best carried out at 120 °C for 4–6 h. Highest acid density of the synthesized catalyst reached 4.56 mmol H + ·g −1 SAC. High oleic acid conversion (∼93%) to methyloleate even at a low temperature of ∼45 °C. Relative activity of the catalyst decreases after reuse, but stabilizes after the 3rd cycle.